Hugh Gregory Gallagher’s Splendid Reception - Barbara Floyd (Disability Studies Quarterly, 2010)
This article assesses the impact of Hugh Gregory Gallagher’s book FDR’s Splendid Deception: The Moving Story of Roosevelt’s Massive Disability — and the Intense Efforts to Conceal It from the Public on our view of America’s only disabled president. The article examines how this book differed from previous biographies of Roosevelt, and how it influenced subsequent portrayals of the president. It focuses on how Gallagher’s study reflected his life experience as a survivor of polio. Particularly, the article looks at how Gallagher recognized what able-bodied historians had not: that despite Roosevelt’s efforts to deceive his family, the public, and himself, he did not "conquer" polio, but rather polio impacted every aspect of the president’s life from the time he contracted it in 1921 until he died in 1945. Finally, it examines the book’s significant influence in shaping how FDR was depicted at the Roosevelt Memorial in Washington, D.C.
Keywords: Hugh Gregory Gallagher; Poliomyelitis; Franklin Delano Roosevelt; Warm Springs; Georgia; Eleanor Roosevelt; Elliott Roosevelt; Roosevelt Memorial; National Organization on Disability